PENINGKATAN MUTU PENDIDIKAN DI MTs ASSALAM dan MTs ISLAMIYAH BANAT TUBAN - istianah, istianah; Burhanuddin, Hamam (At-Tuhfah : Jurnal Studi Keislaman, 2022)
Education is an investment in long-term human resource development and has strategic value for the continuity of human civilization in the world and provision for life in the hereafter. Education is an important part of the national development process which essentially seeks to educate the nation's life and improve the quality of Indonesian people in realizing an advanced, just and prosperous society, and allows its citizens to develop themselves both physically and spiritually. However, there are still some problems in improving the quality of education with various indicators that affect it. This study aims to determine the problems of improving the quality of education at MTs Assalam Bangilan Tuban and MTs Islamiyah Banat Senori Tuban. This type of research is case study research with multi-site studies at MTs Assalam Bangilan Tuban and MTs Islamiyah Banat Senori Tuban. The research used a qualitative approach. Data collection techniques were carried out using interview techniques, observation and documentation. Data analysis techniques use a pragmatic point of view. The research subjects were all elements in the two schools, especially those related to the problems of improving the quality of education. The results showed that there are several problems experienced by MTs Assalam Bangilan Tuban and MTs Islamiyah Banat Senori Tuban. Among them are the lack of teacher motivation, the lack of facilities and infrastructure and the lack of quality human resources, especially in the IT field. Among the efforts to overcome problems to improve the quality of education in MTs Assalam Bangilan Tuban and MTs Islamiyah Senori Tuban is to provide stabilization and work evaluation once a month to all educators. For the lack of facilities and infrastructure, the madrasah asked for help from the surrounding community, especially the santri's guardians to help procure the building. In addition, it can also be done by empowering madrasah alumni who are considered capable and able from each generation. As for the lack of quality human resources, it is overcome by holding special training in the IT field for the staff concerned.